Gender Characteristics of the Course of Rheumatoid Arthritis - Yarmukhamedova Saodat Khabibovna; Khusainova Munira Alisherovna; Khaydarova Zarrina Erkinovna; Kamolova Diyora Djamshedovna (Miasto Przyszłości, 2023)
Rheumatoid arthritis in women is characterized by a more severe course of the pathological process, and the lesion of individual joints depends on the gender of patients (in men, changes in the sacroiliac joints, the development of tendovaginitis, intra-articular Goff bodies are more often noted, and in women — proximal interphalangeal joints of the fingers of the upper and lower extremities, maxillary and knee joints). There is a sexual dimorphism of integral extraarticular (systemic) manifestations of rheumatoid arthritis, while men have more frequent lung and peripheral nervous system damage, and exclusively in the female group — Sjogren's syndrome and changes from the central nervous system. In patients with rheumatoid arthritis, the parameters of bone metabolism in the blood serum change, in addition, in patients with osteoporosis, there are common and gender differences in the concentrations of osteoassociated hormones and chemical elements.